Editions and Publications of Shams-e Tabriz’s Divan: A Critical Review of Research - Rahman Moshtaghmehr (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Maulana’s Divan, alongside the Masnavi, has, for centuries, been a favorite book with circles of “Sama’,” people of taste and mysticism, and lovers of sonnets. The first critical edition of the book, edited by Foruzanfar, was published by University of Tehran in ten volumes, from 1957 to 1965. All following editions of the book have been prepared, publically or in private, according to Foruzanfar’s edition. Some editions carry the names of particular authors on them, while some others bear just the publishers’ names. Alongside these publications, the only reliable editions are those prepared by Professor Sobhani and published by Ghatreh Publications in 2002. The edition includes notes and explanations. The Foruzanfar’sedition, with all its advantages, had its critics, too. One of them was Professor Shafi’i Kadkani who, in his prominent Introduction to his Selections from Maulana’s Divan, suggested the need for another critical edition of the book. Kadkani’s last work on Mowlana’s Divan consisted of two volumes, published in 2009. The expectation was that the selection would be based on a new attitude towards the manuscripts of the text, but apart from a few corrections, the study is entirely based on the Foruzanfar’s edition. This paper deals with the quality of the Foruzanfar’s edition, the editions published before and after it, and Kadkani’s exhaustive edition, from a manuscriptological and editorial skills perspectives.